A Newly Isolated Strain Lysobacter brunescens YQ20 and Its Performance on Wool Waste Biodegradation - Ma, Qinyuan; Zhang, Ya`ning; Zheng, Xue; Luan, Fang; Han, Ping; Zhang, Xianghe; Yin, Yanmiao; Wang, Xiaoxiao; Gao, Xiuzhen (Frontiers in Microbiology, 2022)
The major component of wool is keratin protein, which could be degraded to be free amino acids. Because of its tough secondary structure, wool keratin is difficult to degrade as comparing to feathers. However, to date, only few keratinolytic microorganisms showing high efficiency for wool degradation have been reported. In order to develop an approach for high-value utilization of wool fiber waste, which is produced from shearing, weaving, and industrial processing of wool, screening of wool-degrading bacterium with high degradation efficiency were performed in this study. To this end, Lysobacter brunescens YQ20 was identified and characterized. The optimized conditions for wool degradation were pH 9.0 and 37°C with 20% liquid volume of culture. After fermentation, 15 essential amino acids were detected when wool fiber waste was fermented. The total amino acids produced from 1% wool per hour was 8.6-fold higher than that produced by the strain Stenotrophomonas maltophilia BBE11-1, which had previously been reported to have the highest wool-degrading capacity. Our study reports the first Lysobacter strain that exhibits efficient wool degradation and yields higher concentrations of amino acids than previously reported strains. Whole-genome sequencing indicated that there were 18 keratinase-like genes in the genome of YQ20, which exhibited a long evolutionary distance from those of Bacillus. Therefore, L. brunescens YQ20 may have applications in the environmentally friendly management of wool waste as fertilizer in agriculture.